(untitled) (JSSE - Journal of Science & Sustainable Engineering, 2024)
This article explores the valorization of Amazonian biomass through its conversion into biochar, addressing the main technologies involved and their applications in supercapacitors and catalysts. The conversion of biomass into biochar is highlighted as a sustainable strategy for utilizing agroindustrial waste and generating high-value materials. The article reviews relevant technologies for this conversion, including hydrothermal carbonization, chemical activation, and pyrolysis, emphasizing their impacts on creating biochar with adjustable properties such as high surface area and controlled porosity. It also reviews recent studies investigating the valorization of Amazonian biomass for these specific applications, highlighting the advances made. Finally, future perspectives are discussed, including the exploration of new Amazonian biomass sources and the optimization of conversion techniques to expand biochar applications and promote technological innovation and sustainability in the Amazon region.